2019
DOI: 10.33714/masteb.547103
|View full text |Cite
|
Sign up to set email alerts
|

The Reflection of Ship Demolition Prices to Construction Costs in Turkey

Abstract: The ship demolition sector is one of the major suppliers of the steel market, even though its share in the total scrap market is very small. As the sector is a supplier of the steel market, it is inevitable that the price changes will be reflected in the construction sector, which is one of the largest steel customers. In this context, it is aimed in this study to determine whether the changes in demolition prices of Turkey, which is one of the main ship demolition locations in the world, have an effect on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This has also been empirically tested and confirmed by Kagkarakis, Merikas and Merika [2016] and Tunç and Açık [2019]. Due to this close relationship, ship demolition prices can also affect construction costs, as investigated by Açık and Baran [2019]. However, this effect may be due to its close relationship with the steel market rather than the direct effect of the ship demolition price.…”
Section: Industry Overview and Literature Reviewmentioning
confidence: 72%
“…This has also been empirically tested and confirmed by Kagkarakis, Merikas and Merika [2016] and Tunç and Açık [2019]. Due to this close relationship, ship demolition prices can also affect construction costs, as investigated by Açık and Baran [2019]. However, this effect may be due to its close relationship with the steel market rather than the direct effect of the ship demolition price.…”
Section: Industry Overview and Literature Reviewmentioning
confidence: 72%
“…Mikelis (2007) also evaluated that this relationship could be positive by statistical analysis. Undoubtedly, the price of demolition should be also related to variables other than maritime, because the steel from demolition is used as input to some sectors, such as the construction sector (Açık and Baran, 2019). Kagkarakis et al (2016) examined the relationship between ship demolition prices and global scrap prices and found that global scrap prices are decisive for ship demolition prices since their small share in the global steel industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most important customers of the steel sector is the construction sector, which is likely to be affected by the ship demolition market. In a study conducted on this research question, the impact of Turkish ship demolition prices on construction costs in Turkey examined (Açık and Baran, 2019) and it was found that positive shocks in ship demolition prices cause positive shock in the construction costs. This suggests that the ship demolition market may be effective in the costs of steel users, albeit its small size in the market.…”
Section: Literature Reviewmentioning
confidence: 99%